Ideologi dan Wacana Kognisi Keagamaan di Pondok Pesantren Tradisional dalam Gema Santri - Nazla Maharani Umaya (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This article discusses the findings of the ideology and religious attitudes through the perceptions of students on the work of the literary expression as a form of discourse and cognition in the traditional boarding schools. Research literature this is a stage of advanced exploration and study results of mentoring, the development potential of the students in the form of an anthology of short stories, â€œGema Santriâ€. Research methods in the form of a descriptive study ekploratory literature. The purpose of the research was elaborated the discourse ideology and cognition of the traditional boarding schools students in Semarang city, based on research, as one of the areas adjacent to the cityâ€™s guardian (kota Wali). The research benefits gives an overview on the public discourse about ideology and cognition discourse based boarding schools traditionally. And that is proven dynamic and able to co-exist with modernization. The context is the social and ideological as the concept of the nature human beings as social beings. The findings is the content of education and behavior in boarding schools far away from the traditional perception of ideology and cognition discourse, fanatics, and thus is dynamic in generating a generation of nationalists, dynamic, and multicultural.